Solid Forms of Tenofovir Disoproxil Fumarate, Their Mutual Conversion, and Stabilization of Form I in Formulation - Sládková, Veronika; Dammer, Ondřej; Kratochvíl, Bohumil (Journal of pharmaceutical sciences, 2016)
Tenofovir disoproxil fumarate (TDF, form I) is an orally delivered pharmaceutical salt used for the treatment of HIV and chronic hepatitis, which acts as an inhibitor of nucleotide reverse transcriptase. There are many solid forms of TDF described in the literature; 2 of them were identified in the drug products: form I and form A. It seems that during formulation, the active pharmaceutical ingredient undergoes partial to total conversion of TDF form I to TDF form A. The goals of this study were to investigate when and why did the conversion occur and whether the conversion could be avoided and how. The influence of pH and possible interaction with excipients were studied. The conditions enabling using wet granulation in technology while preventing the undesired conversion were found. The stabilization was achieved either by replacement of used disintegrants or by acid addition to the current composition of formulation.
Keywords: Tenofovir; formulation; pomocné látky; látky proti HIV; difrakce rentgenového záření; cocrystals; Excipients; Hydrogen-Ion Concentration; X-ray powder diffractometry; Drug Stability; tenofovir; koncentrace vodíkových iontů; X-Ray Diffraction; crystal polymorphism; stabilita léku; Drug Compounding; drug-excipient interaction; příprava léků; Anti-HIV Agents